Morphological and phylogenetic evidence for the transfer of the monotypic genus Tordyliopsis to Semenovia (Apiaceae) - Guo, Xian-Lin; Xiao, Qun-Ying; Gou, Wei; Zhou, Song-Dong; He, Xing-Jin (Phytotaxa, 2023)
Tordyliopsis is a monotypic genus within the family Apiaceae and is endemic to the southern margin of the Himalayas. The type species, Tordyliopsis brunonis, is easily distinguished by its lanceolate bracts and bracteoles. In this study, we used both phylogenetic and morphological analyses to investigate the relationship between T. brunonis and other species in the Apiaceae. Our phylogenetic analyses of ITS sequences and 79 coding sequences from complete plastid genomes revealed that T. brunonis is nested with Semenovia species. Additionally, our morphological analysis showed that Tordyliopsis and Semenovia share several similar features, including elliptic or oblong mericarps with widely spaced dorsal ribs, broader and winged marginal ribs with slightly inflated distal parts, clavate vittae, and domed stylopodium. Based on these results, we propose that the monotypic genus Tordyliopsis should be transferred to Semenovia.